THE POWER OF TRUST: ANALYZING THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND TRUST ON LOCAL SKINCARE PURCHASING DECISIONS - Patrecia, Joice; Heng, Lie (SEGMEN: Jurnal Manajemen dan Bisnis, 2026)
This study examines the effect of social media marketing on the purchase decision of local skincare products, with brand trust as a mediating variable. The increasing interest of Indonesian millennials and Gen-Z in local products is due to influencers, price, packaging, and product suitability. Data was collected from 125 students in Pontianak through questionnaires and interviews, then analyzed using AMOS.The results show that social media marketing has a significant effect on brand trust, which in turninfluences purchasing decisions. Brand trust was also found to mediate the relationship between social media marketing and purchasing decisions. These findings highlight the importance of building brand trust through social media strategies to increase consumer confidence and drive sustainable marketgrowth